Steroid Treatment in Hematologic Patients with COVID-19: Experience of 2 cases - Jlal Bathish; Ayat Zabida; Lihie Eisenberg; Lee Cohen Ben-Meir; Aliza Zeidman (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
On March 2020, Hasharon hospital reopened as the first and solely COVID-19 hospital in Israel. For six weeks 52 positive COVID-19 patients were admitted to our ward, Corona B ward. According to previous publications, patients with coexisting hematological condition were more vulnerable to COVID-19 complications. In particular, corticosteroids treatment was reported to reduce the cytokine storm complication of COVID-19. Yet, the literature regarding corticosteroids treatment was controversial at that time. We present two positive COVID-19 hemato-oncologic patients with successful treatment with corticosteroids: a patient with active Chronic Lymphocytic Leukemia (CLL) and a patient with Hodgkin Lymphoma (HL). Epidemiological, clinical, laboratory, imaging and treatment course are discussed along with the relevant literature.